2015
DOI: 10.1371/journal.pone.0128329
|View full text |Cite
|
Sign up to set email alerts
|

Blame the Patient, Blame the Doctor or Blame the System? A Meta-Synthesis of Qualitative Studies of Patient Safety in Primary Care

Abstract: ObjectiveStudies of patient safety in health care have traditionally focused on hospital medicine. However, recent years have seen more research located in primary care settings which have different features compared to secondary care. This study set out to synthesize published qualitative research concerning patient safety in primary care in order to build a conceptual model.MethodMeta-ethnography, an interpretive synthesis method whereby third order interpretations are produced that best describe the groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
93
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 83 publications
(283 reference statements)
3
93
0
5
Order By: Relevance
“…Portanto, para que haja desenvolvimento da assistência de forma eficaz e segura, a comunicação merece ser precisa tanto entre membros da equipe setorial quanto intersetorial, sendo o alicerce das relações, bem como um elemento essencial à prática do cuidado humanizado, integral e reduzido de danos ao paciente. 8,18 Não menos importante, os resultados descritos no item G11 (Tabela 4), em relação à passagem de plantão, dispõe que 46,3% dos profissionais discordam que as mesmas são problemáticas para o paciente no referido hospital, se contradizem com relação à G5, onde 52,9% dos trabalhadores afirmam que informações importantes sobre o cuidado ao paciente se perdem com frequência durante as passagens de plantão.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Portanto, para que haja desenvolvimento da assistência de forma eficaz e segura, a comunicação merece ser precisa tanto entre membros da equipe setorial quanto intersetorial, sendo o alicerce das relações, bem como um elemento essencial à prática do cuidado humanizado, integral e reduzido de danos ao paciente. 8,18 Não menos importante, os resultados descritos no item G11 (Tabela 4), em relação à passagem de plantão, dispõe que 46,3% dos profissionais discordam que as mesmas são problemáticas para o paciente no referido hospital, se contradizem com relação à G5, onde 52,9% dos trabalhadores afirmam que informações importantes sobre o cuidado ao paciente se perdem com frequência durante as passagens de plantão.…”
Section: Resultsunclassified
“…7 Na área da saúde, que se constitui num peculiar setor de prestação de serviços, a comunicação tem potencial para subsidiar o cuidado integral e humanizado, e por isso, infere-se que este é um fator que merece atenção à promoção do atendimento seguro em todos os níveis de atenção. 8 Isso porque, falhas nas linhas de comunicação podem favorecer a ocorrência de eventos adversos, 5 que são definidos como incidentes produzidos pelo processo de cuidado que resultam em dano real, de magnitude variada, à saúde do usuário. 2 Especialmente no contexto hospitalar, em que o risco associado à assistência é mais evidente, as linhas de comunicação entre profissionais e/ou setores podem ser um elemento de dificuldade à sua eficácia.…”
Section: Introductionunclassified
“…‘Blame the Patient, Blame the Doctor or Blame the System? A Meta‐Synthesis of Qualitative Studies of Patient Safety in Primary Care’, PLoS ONE , 10.8 (): e0128329. Web.…”
mentioning
confidence: 99%
“…Some simple interventions, such as introduction of mandatory safe surgery checklists to prevent adverse surgical events (2,3), optimizing antimicrobial use and implementing appropriate hand-hygiene practices to prevent hospital acquired infections (4) have been shown to be useful, but the compliance is not always optimal and difficult to sustain (5), whereas the usefulness of some other resource-consuming procedures, such as adverse event or incident reporting and disclosure systems, remains uncertain (6). Some simple interventions, such as introduction of mandatory safe surgery checklists to prevent adverse surgical events (2,3), optimizing antimicrobial use and implementing appropriate hand-hygiene practices to prevent hospital acquired infections (4) have been shown to be useful, but the compliance is not always optimal and difficult to sustain (5), whereas the usefulness of some other resource-consuming procedures, such as adverse event or incident reporting and disclosure systems, remains uncertain (6).…”
mentioning
confidence: 99%
“…There are a number of institutions and advocacy groups that evaluate evidence and/or provide guidance on patient safety issues. Some simple interventions, such as introduction of mandatory safe surgery checklists to prevent adverse surgical events (2,3), optimizing antimicrobial use and implementing appropriate hand-hygiene practices to prevent hospital acquired infections (4) have been shown to be useful, but the compliance is not always optimal and difficult to sustain (5), whereas the usefulness of some other resource-consuming procedures, such as adverse event or incident reporting and disclosure systems, remains uncertain (6). A recent systematic review found that although incident reporting systems may enable organizational learning, they did not perform better than other methods and had little effect on improving patient outcomes (7).…”
mentioning
confidence: 99%